The Magnificent Ruins - Roy, Nayantara, 1985- (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2024)
"When Lila, a rising 29-year-old Indian American editor based in Brooklyn, unexpectedly inherits a huge ancestral home in the center of Calcutta, she must return to India, where she must also confront her mother after a decade's estrangement, along with her grandmother, and extended family, all of whom still live in the house, and resent her sudden legacy"--.
new book 2024 fall.
Keywords: Estranged families; East Indian American women; Homecoming; Domestic fiction; Family secrets; East Indian Americans; Inheritance and succession; Kolkata (India); Domestic fiction; Novels